The Relationship Between Post-Traumatic Stress Disorder and Autism for Children Under 10 Years, Parents’ Perspective: A Case Control Study - Ahmed Hassan Alhussaini; Maytham Salim AL-Nasrawii (National Journal of Community Medicine)
Background: Post-Traumatic Stress Disorder (PTSD) occurs as a result of exposure to stressful events such as assaults, accidents, and disasters and poses a significant risk to a child’s mental health. Children with Autism Spectrum Disorder (ASD) are at a higher risk of developing PTSD compared to their neurotypical peers. This research aimed to investigate the correlation between PTSD & ASD in children under 10 years old.